Limitations of mouse models for sickle cell disease conferred by their human globin transgene configurations - Kaitly J. Woodard; Phillip A. Doerfler; Kalin D. Mayberry; Akshay Sharma; Rachel Levine; Jonathan Yen; Virginia Valentine; Lance E. Palmer; Marc Valentine; Mitchell J. Weiss (The Company of Biologists, 2022)
We characterized the human β-like globin transgenes in two mouse models of sickle cell disease (SCD) and tested a genome-editing strategy to induce red blood cell fetal hemoglobin (HbF; α2γ2). Berkeley SCD mice contain four to 22 randomly arranged, fragmented copies of three human transgenes (HBA1, HBG2-HBG1-HBD-HBBS and a mini-locus control region) integrated into a single site of mouse chromosome 1. Cas9 disruption of the BCL11A repressor binding motif in the γ-globin gene (HBG1 and HBG2; HBG) promoters of Berkeley mouse hematopoietic stem cells (HSCs) caused extensive death from multiple double-strand DNA breaks. Long-range sequencing of Townes SCD mice verified that the endogenous Hbb genes were replaced by single-copy segments of human HBG1 and HBBS including proximal but not some distal gene-regulatory elements. Townes mouse HSCs were viable after Cas9 disruption of the HBG1 BCL11A binding motif but failed to induce HbF to therapeutic levels, contrasting with human HSCs. Our findings provide practical information on the genomic structures of two common mouse SCD models, illustrate their limitations for analyzing therapies to induce HbF and confirm the importance of distal DNA elements in human globin regulation. This article has an associated First Person interview with the first author of the paper.